(untitled) (Fiep Bulletin - online, 2024)
ABSTRAT Gyms currently offer various forms of exercise, thus becoming a space for non-formal education, seeking to provide their clients with various activities, especially “care” for their bodies. The objective of the study was to carry out a literature review about personalized services in gyms. Data collection took place by searching the following databases: SCIELO and LILACS, from 2010 to 2020. The articles, the title, abstract and, when necessary, the full text were analyzed. After the initial analysis and selection of articles, manual analysis took place where the selection was based on compliance with the theme of this study, with those that, despite appearing in the search results, not specifically addressing the subject of the study being disregarded. As a result, the reasons that lead people to go to gyms to practice physical exercise are the presence of the Personal Trainer, adherence and training time in clients’ Personalized Training programs, the Personal Trainer predominantly has female clients, with varying ages, the gyms currently have the presence of a personal trainer with a degree in Physical Education. It was possible to conclude that the reasons that lead people to go to gyms to practice physical exercise are the presence of the Personal Trainer, adherence and training time in clients’ Personalized Training programs. predominantly female clients, with varying ages, while men who seek personalized training are older than women, with an average of 35 years old, for clients, the development of strategies in personalized training, promotes motivation and loyalty in classes, and the certainty that they are on the path to good health. Keywords: Academies. Personal trainer. Customized training.